Pembatalan Peraturan Daerah dan Akibat Hukumnya Menurut Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Victor Juzuf Sedubun; Marthinus Johanes Saptenno; Jemmy Jefry Pietersz; Sostones Yacobis Sisinaru (SASI, 2019)
Based annulment nomenclature that used in Article 251 paragraph (1) and paragraph (2) may be canceled under vernietigbaar category. Vernietigbaar or ex nunc, means that the annulment is effective at that immidiate time. The legal consequences of cancellation pursuant to Article 251 paragraph (1) and paragraph (2) are considered to exist until there is a revocation by the Local Government. This is in accordance with the principle and the principle praesumptio iustae causa and contrarius actus. the changes to the legislation in the field of local government is very important. Additions are required in relation to the establishment of the Local Regulation, as mandated in Article 18B paragraph (1) NRI Constitution of 1945, and Act No. 23 of 2014. The Act No. 23 of 2014 does not specify clearly the procedures for the supervision and control parameters of the Local Regulation.